(untitled) (The Research of Medical Science Review, 2025)
Objective: to evaluate the role of magnetic resonance imaging MRI in clinical diagnosis of lumber disc herniation. Clinical settings: Islamabad Diagnostic Center, Faisalabad. Study duration: September 2024 to December 2024. Study design: Observational Cross sectional study. Method: MRI lumber spine scans were performed on 100 patients according to inclusion criteria. T1sagittal, T2 sagittal, STIR sagittal, T1 axial and T2 axial images were acquired with Phillips 1.5 Tesla MRI scanner. Interpretation of these images was done by Consultant Radiologists who had experience of reporting of lumber spine. Data was extracted systemically from each scan and analysis was done on statistical package for social sciences version 23. Frequencies and graphs were obtained for ever demographic variable. Results: Patient includes 66 females and 44 males. Lumber disc herniation was more prevalent in female patients of age group 30-40. In 94% cases lower back pain is most common symptom while only 12% was affected by trauma.77% patients complain of radiating lower back pain toward legs. 57% cases shows nerve compression due to disc bulge. 77% patients are observed with disc bulge. 40% patients are diagnosed with muscular spasm. 66% cases are observed with spine straightening. Conclusion: MRI plays a critical role in the diagnosis of lumbar disc herniation. Understanding the diagnostic process can help patients and healthcare professionals work together to achieve accurate diagnosisand effective treatment.